The Export-Performance Licensing Scheme (The Pakistan Development Review, 1970)
The structure and impact of the Export-Performance Licensing Scheme is a particularly interesting study when contrasted with the Export Bonus Scheme. These two export-incentive measures overlap in many ways; yet they are radically different in certain aspects. Each alone has evolved administratively into a formidable institutional structure. The Export Bonus Scheme has been based upon a partially market-oriented, price-determined allocation of resources. However, the Export-Performance Licensing Scheme has been directly con¬trolled by administrative intervention at all levels. It is interesting to search for reasons why the Export-Performance Licensing Scheme has reached a condition such that the following comments could be seriously posited: